Use of an Endobronchial Blocker in a Patient with Tracheobronchial Anomaly for Minimally Invasive Cardiac Surgery: A Case Report - Emine Nilgün Zengin; Nevriye Salman; Ayşegül Özgök (Turkish Journal of Anaesthesiology and Reanimation, 2024)

(untitled)
Tracheal bronchi (TB) is a rare anomaly and is usually asymptomatic. Although it is generally not a problem when a single lumen tube is used, it may cause ventilation difficulties in the intraoperative period in procedures requiring one lung ventilation, such as minimally invasive cardiac surgery. Therefore, these difficulties may cause intraoperative and postoperative complications. While a double-lumen tube is recommended as the primary choice for one-lung ventilation in patients with TB, bronchial blockers can be used to avoid the need for tube exchange in patients who will remain intubated in the postoperative period.